Reply to: Proton Pump Inhibitors and Long‐term Risk of Community‐acquired Pneumonia in Older Adults. Issue 12 (16th October 2018) - Ble, Alessandro; Zirk‐Sadowski, Jan; Masoli, Jane A.
Abstract : This letter comments on the letters byAyele et al andRichard Schreiber